Lexicаl-Semantic and Syntactic Valency of Language Representations of the Emotional World in the Poem “Then, fare thee well” by T. Mооre - A. V. Diehl (Дискурс, 2021)
Introduction. The article is devoted to the study of the specificity of the lexical-semantic and syntactic valency of lexical units nominating emotions in the poem “Then, fare thee well” by T. Moore. The relevance of this study lies in the fact that it has been carried out in line with the linguo-cognitive paradigm and aims to identify the specifics of the compatibility of emotions nominations with other lexical units verbalizing the fragment of the concept “the emotional world”. The novelty of the research is associated with its anthropocentric orientation and interdisciplinary nature of the interpretation of the material, which implies the study of the artistic concept sphere “the emotional world” on the material of the poem “Then, fare thee well” by T. Moore from the standpoint of cognitive linguistics, psychology and literary criticism.Methodology and sources. The theoretical basis of this research is presented by the works of scientists V.Yu. Apresjan, E.V. Galeeva, N.A. Krasavskii, I.N. Kucher, S.G. Lyubova, K.O. Pogosova, E.A. Rozhnova, who considered the essence of emotional concepts as culturally conditioned mental constructs, i.e. directly related to the worldview of representatives of a particular ethnic group.In the article we use the following research methods: the method of definitional analysis, the functional-semantic method, the method of component analysis, the descriptive method, as well as methods of continuous sampling and quantitative data processing.Results and discussion. In the present study, the classification of lexical units verbalizing the manifestations of emotional states in the poem “Then, fare thee well” by T. Moore has been made. In the semantic structure of the lexemes under consideration, we highlight and categorize the semes marked by the correlation with the emotional sphere of people. The linguo-cognitive analysis of the lexic and syntactic valency of the primary and secondary nominations of emotions, carried out in the work, revealed the specifics of the conceptualization of emotional states and experiences in the individual author's picture of the world.Conclusion. It has been established that the artistic conceptual sphere “emotional world” in the poem “Then, fare thee well” by T. Moore consists of two closely interrelated concepts – “negative emotions” and “positive emotions”, verbalized by lexemes nominating a wide range of emotional experiences of the lyrical character. It is concluded that the associative-figurative characteristics attributed to a specific emotion in the artistic world of the author carry valuable culturally relevant information about the individual characteristics of the interpretation of emotional concepts both by the poet himself and by the “naïve” thinking of an English-speaking person as a representative of his language and culture.